Distributive Property All Positive

Simplify the following expression: 2(x+1) = Simplify the following expression: 3(x+3) = Simplify the following expression: 2(x+8) = Simplify the following expression: 4(x-5) = Simplify the following expression: 5(2x-1) = Simplify the following expression: 7(3x+2) = Simplify the following expression: 4(x+5) = Simplify the following expression: 8(x+3) = Simplify the following expression: 4(3x+6) = Simplify the following expression: 7(2x+9) = Simplify the following expression: 4(11b + v) = Simplify the following expression: 9(7t + b) = Simplify the following expression: 5(7z + 10) = Simplify the following expression: 6(6r + 10u) = Simplify the following expression: 2(4y + k) = Simplify the following expression: 5(2 + 10g)= |

Students who took this test also took :

Created with That Quiz —
the math test generation site with resources for other subject areas.